Peningkatan Keterapilan Membaca Permulaan Menggunakan Media Kartu Kata Dalam Pembelajaran Bahasa Indonesia pada Siswa kelas 1 SDN 2 Gunungkendeng - Musiah; Lia Rismawati; Mohammad Irfan (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to improve the early reading skills of first-grade students at SDN 2 Gunungkendeng through the use of word card media in Indonesian language instruction. The background of this research lies in the students' low early reading abilities, which are attributed to conventional teaching methods and the lack of engaging instructional media. This research employed a Classroom Action Research (CAR) approach with a quantitative method, conducted over two cycles. The subjects consisted of 20 first-grade students, comprising 14 boys and 6 girls. Data collection techniques included observation, testing, and documentation, with data analysis using the percentage of learning mastery. The results showed that the use of word card media significantly enhanced students' early reading skills. In the pre-cycle phase, only 25% of students achieved learning mastery. After the intervention in the first cycle, this percentage increased to 70%, and further improved to 85% in the second cycle. These findings indicate that word card media is effective in enhancing student engagement and learning outcomes in early reading for first-grade students. In conclusion, the use of word card media in Indonesian language learning can gradually and significantly improve students’ early reading skills.